Qachwa: Cultural wealth of Angaraes – Huancavelica - Caso Álvarez, Jesús Guillermo (2021)
One of the lyrical species of Quechua origin is called Qachwa, which in Castilian would be dance, music and song of ancestral origin and that lasts in Huancavelica until today. Likewise, the cultural identity of the huancavelicano settlers is deeply rooted, whose preservation is of the greatest importance. So, it is correct to say that, if this species remained unscathed, it is thanks to the unbreakable cultural identity so fervently maintained. In this research work, the relationship that exists between the variable Qachwa: Intangible Cultural Heritage and cultural Identity in Huancavelica has been investigated. The objective followed was to demonstrate how the Qachwa as intangible heritage is related to the cultural identity in Huancavelica. As regards methodological, it is of a basic type, with a descriptive method and correlational design, with a probability sampling. The result was surprising, according to the application of a Likert-type survey. 58% of respondents mentioned that Qachwa is their intangible heritage, therefore, 56% of them agree to maintain their cultural identity. Consequently, the more the Qachwa is considered to be a precious intangible heritage, the cultural identity of the Huancavelicans is consolidated to preserve and conserve their aforementioned identity.